Novel Therapeutic Approach for Obesity: Seaweeds as an Alternative Medicine with the Latest Conventional Therapy - Rajesh Yadav; Ankita Nigam; Richa Mishra; Saurabh Gupta; Anis Ahmad Chaudhary; Salah-Ud-Din Khan; Eman Abdullah almuqri; Zakir Hassain Ahmed; Sarvesh Rustagi; Deependra Pratap Singh; Sanjay Kumar (Medical Sciences)
The prevalence of overweight and obesity is increasing worldwide. Common comorbidities related to obesity, significantly polygenic disorders, cardiovascular disease, and heart conditions affect social and monetary systems. Over the past decade, research in drug discovery and development has opened new paths for alternative and conventional medicine. With a deeper comprehension of its underlying mechanisms, obesity is now recognized more as a chronic condition rather than merely a result of lifestyle choices. Nonetheless, addressing it solely through lifestyle changes is challenging due to the intricate nature of energy regulation dysfunction. The Federal Drug Administration (FDA) has approved six medications for the management of overweight and obesity. Seaweed are plants and algae that grow in oceans, rivers, and lakes. Studies have shown that seaweed has therapeutic potential in the management of body weight and obesity. Seaweed compounds such as carotenoids, xanthophyll, astaxanthin, fucoidans, and fucoxanthin have been demonstrated as potential bioactive components in the treatment of obesity. The abundance of natural seaweed bioactive compounds has been explored for their therapeutic potential for treating obesity worldwide. Keeping this view, this review covered the latest developments in the discovery of varied anti-obese seaweed and its bioactive components for the management of obesity.